Analysis of Digital Marketing Strategy in Increasing Sales at Murai Coffee Gunungsitoli - Mendrofa, Soterman Fotendo Kristian; Bate’e, Maria Magdalena; Harefa, Idarni; Gulo, Heniwati (PT. Maju Malaqbi Makkarana, 2025)
This research is motivated by the phenomenon of suboptimal digital marketing strategies implemented by Murai Coffee Gunungsitoli, which have resulted in decreased visibility and sales. The research objective is to analyze the implemented strategies, identify challenges, and formulate optimal strategies to increase sales. The approach used is qualitative with interview, observation, and documentation techniques, as well as descriptive data analysis. The results show that previous digital marketing strategies have contributed to increased visibility, but have not been managed consistently and creatively. Challenges faced include limited resources, content planning, and audience interaction. Research recommendations include content consistency and innovation, optimization of social media features, and regular evaluation of digital campaigns to encourage buying interest and sustainable sales